Artificial intelligence for optimizing benefits and minimizing risks of pharmacological therapies: challenges and opportunities - Crisafulli, Salvatore; Ciccimarra, Francesco; Bellitto, Chiara; Carollo, Massimo; Carrara, Elena; Stagi, Lisa; Triola, Roberto; Capuano, Annalisa; Chiamulera, Cristiano; Moretti, Ugo; Santoro, Eugenio; Tozzi, Alberto Eugenio; et al. (Frontiers in Drug Safety and Regulation, 2024)
In recent years, there has been an exponential increase in the generation and accessibility of electronic healthcare data, often referred to as “real-world data”. The landscape of data sources has significantly expanded to encompass traditional databases and newer sources such as the social media, wearables, and mobile devices. Advances in information technology, along with the growth in computational power and the evolution of analytical methods relying on bioinformatic tools and/or artificial intelligence techniques, have enhanced the potential for utilizing this data to generate real-world evidence and improve clinical practice. Indeed, these innovative analytical approaches enable the screening and analysis of large amounts of data to rapidly generate evidence. As such numerous practical uses of artificial intelligence in medicine have been successfully investigated for image processing, disease diagnosis and prediction, as well as the management of pharmacological treatments, thus highlighting the need to educate health professionals on these emerging approaches. This narrative review provides an overview of the foremost opportunities and challenges presented by artificial intelligence in pharmacology, and specifically concerning the drug post-marketing safety evaluation.